Edoxaban treatment in real-world practice is highly concordant with ESC atrial fibrillation guidelines: results from the non-interventional global ETNA-AF program. (14th October 2021) - Morrone, D; Chen, C; Dinshaw, L; Jiang, W; Kim, Y.-H; Kirchhof, P; Koretsune, Y; Pecen, L; Reimitz, P.-E; Wang, C.-C; Yamashita, T; Unverdorben, M; et al.
Abstract: Background: The ESC atrial fibrillation management guidelines recommend a risk-based approach to oral anticoagulant (OAC) therapy. How clinical practice aligns with these recommendations is of interest. Purpose: To analyse real world data from Global ETNA-AF program in patient groups stratified by stroke and bleeding risk scores according to ESC guidelines. Methods: Global ETNA-AF is a multicentre, prospective, noninterventional program evaluating the safety and effectiveness of edoxaban in patients from European and Asian countries. Baseline characteristics and clinical event data at 2-year follow-up were analysed in 4 subgroups defined by CHA2DS2-VASc score (≥3 for female / ≥2 for male [OAC recommended] vs 2 for female / 1 for male [OAC should be considered]) and HAS-BLED score (≥3 [Bleeding risk high] vs <3 [Bleeding risk low]) (Table 1). Results: Of 27, 616 patients included in this analysis, 23, 152 (83.8%) were in the "OAC recommended" category and 3, 539 (12.8%) were in the "OAC should be considered" category. Only 3.3% of patients did not meet ESC guideline criteria for OAC initiation. Among patients with high bleeding risk, 98% were in the "OAC recommended" category. A similar distribution was observed across regions (Table 2). The recommended edoxaban dose was used in the vast majority (>80%) of patients across all risk stratification subgroups. In the "OAC recommended" category, patients with high bleeding risk had higher rates of thromboembolic, bleeding, and death events than those with low bleeding risk. Conclusion: Data from routine clinical practice in Global ETNA-AF demonstrate high concordance of edoxaban treatment with ESC guidelines. Edoxaban dose is consistent with label recommendation in the vast majority (>80%) of patients. Clinical event rates were generally low across all risk groups, including acceptable bleeding rates in anticoagulated patients with high bleeding risk. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Daiichi Sankyo